Students of MTSN Wonogiri: Psicology Perspectiveof Islamic Education: Siswa Berbakat MTSN Wonogiri: Perspektif Psikologi Pendidikan Islam - Suparman, Suparman (Journal of Islamic and Muhammadiyah Studies, 2020)
The term gifted is described by Renzulli that there are interactions that unite the three main characteristics (three rings conception), namely general abilities with levels above the average normal child, creativity above average, self-attachment to tasks is quite high. Gifted children have the ability to develop a combination of the three characteristics. The purpose of this study was to determine the condition of gifted students and analyze the development of giftedness in MTsN Wonogiri Regency. This research is a field research designed to find out the development of gifted stu- dents at MTsN Wonogiri, Central Java. The research design uses qualitative analysis with a multidisciplinary approach. This study besides describing ethnographically the school under study in the research location, as well as trying to dismantle and understand the hidden ideas of the development of gifted students at school. The results of this study are (1) MTsN 1 Wonogiri, MTsN Nguntoronadi, and MTsN Purwantoro are Islamic Education Institutions under the auspices of the Ministry of Reli- gion of Wonogiri Regency who pay attention to the development of student giftedness, through initial selection of school entry, learning processes, evaluations, extracurricular activities and stakeholders, (2) Analysis of student gifted development in the form of char- acteristics, namely average ability; general ability, special ability, commitment to the task.